Supplementation with Korean Red Ginseng Improves Current Perception Threshold in Korean Type 2 Diabetes Patients: A Randomized, Double-Blind, Placebo-Controlled Trial - Kahui Park; YuSik Kim; Junghye Kim; Shinae Kang; Jong Suk Park; Chul Woo Ahn; Ji Sun Nam (Journal of Diabetes Research)
Background. Many Type 2 diabetes (T2DM) patients in Korea take Korean Red Ginseng (KRG) for various reasons. In this study, we investigated the effects of KRG administration on diabetic peripheral neuropathy in T2DM patients. Methods. This study was a randomized, double-blind, placebo-controlled trial. Participants were randomly allocated to either the placebo or KRG group and took corresponding tablets for 24 weeks. The primary outcomes were changes in current perception threshold (CPT) at week 24. Secondary outcomes were altered fasting plasma glucose, HbA1c, and various metabolic and inflammatory markers at week 24. Results. Sixty-one patients completed the study. The CPT of the lower extremities at various frequencies exhibited significant improvements at week 24 in the KRG group. Other metabolic parameters were not altered after 24 weeks in both groups. In the subgroup analysis, CPT levels were improved in those with a longer diabetes duration or who already had neuropathy at the beginning of the study, and insulin resistance was improved in patients with a shorter diabetes duration. Conclusion. Twenty-four week administration of KRG in T2DM patients resulted in a significant improvement in neuropathy, especially in those with a longer diabetes duration. A further, larger population study with a longer follow-up period is warranted to verify the effects of KRG on diabetic neuropathy.